Characterization of crack profile of damaged plain concrete - Cammayo, Krystel Isabel U.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Experiments were performed to obtain actual crack profiles. Nine concrete specimens were subjected to three-point loading until fracture and only the final cracks were observed. Three concrete mixtures with the same aggregates were used to investigate the effect of varying compressive strength of the concrete on the crack geometry. The crack profiles were acquired using surface metrology techniques; cracks were digitized using a scanning device, and the coordinates were obtained using 3D graphics software. The crack geometric properties such as tortuousity and roughness were then calculated. Results show that tortuosity values increases as the strength of the concrete increases. The reported values are 0.85, 0.86 and 0.87 for concrete with compressive strengths of 20, 25 and 30MPa, respectively. The roughness, however, have high variation; values of which range from 1.20 to 7.60. There was no relationship between the strength of concrete and roughness established. Statistical analysis on the crack geometry was carried out to identify the parameters that can be used to generate profiles depicting realistic cracks. A single crack profile consists of series of segments. The variables observed were the segment length and the deviation angle. It was established the angle values follow a nonnal distribution while the length values follow Johnson distribution. The mean and standard deviation of the two variables were computed and averaged per strength and were used to create the crack-generating model. The results of this study can be used for fluid flow computations and verify the results of the experimental study conducted by other researchers.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Cracking